Iconography and hybridity in the epic film Hikayat Merong Mahawangsa (2011) / Al Mubarakah Suleiman - Suleiman, Al Mubarakah (2020)
This study aims at examining the elements of iconography in the epic film Hikayat Merong Mahawangsa directed by Yusry Abdul Halim in 2011. The film was adapted from classic Malay literature, Hikayat Merong Mahawangsa, which was written in the 18th to 19th century. This study argued that the film adopted a hybrid approach, which in this context of the study refers to the term of combining the elements of epic iconography or other influences to create a new meaning or ideology. The objectives of this study are to identify the elements of iconography such as settings, props, costume, makeup, hair and special effects from both the Malay Hikayat and Hollywood blockbusters as well as to interpret the elements of iconography in the film Hikayat Merong Mahawangsa (2011) concerning its original literary text, Hikayat Merong Mahawangsa. This study was conducted through a textual analysis method of mise en scene with the theoretical framework of Homi K. Bhabha’s hybridity of culture and the merged of Daniel Chandler’s classifications of genre convention with Constatine Santa’s formal qualities of the epic film. It was found that the film Hikayat Merong Mahawangsa was a loose adaptation of the original literary text; however, with the basic adaptation of the original text, this film employed a hybrid approach with the influences of Hollywood epics and conventions in Malay literature. Therefore, with the elements of iconography from both medium of Malay literature and Hollywood epics, the film has created a new dimension in the local epic film. Based on Bhabha’s theory on hybridity on cultures, the film, Hikayat Merong Mahawangsa also employed a cultural hybridisation, as the film represents the Malay identity with the merging of multiracial cultures and influences through elements of iconography. This film was culturally hybridized as a cross-genre of the epic and comedy, as well as war and romance that stands on its own and was different from previous local epics such as Hang Tuah (1955), Raja Bersiong (1968) or Puteri Gunung Ledang (1994). Overall, the study is significant as it contributes to researches on the iconography of the epic film Hikayat Merong Mahawangsa (2011) and provides information on hybrid approaches in film iconography that can be applied in future film making.